Pelatihan Dasar-Dasar Layanan di Restoran Bagi Siswa-Siswi Yayasan Emmanuel: Kebersihan dan Sanitasi - Adato, Vasco; Yuliantoro, Nonot; Situmorang, Jimmy; Hassan, Rayyani; Sunar, Steven (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Basic Service Training Activities in Restaurants for Emmanuel Foundation Students: Hygiene and Sanitation In the tourism sector, especially for those who work in this sector, it is essential to carry out personal hygiene and sanitation of the work environment. Regarding standards in carrying out and maintaining personal hygiene and sanitation, especially in a restaurant or hotel that aims to meet customer satisfaction. Basic service training in restaurants for students of the Emmanuel Foundation regarding the importance of personal hygiene and sanitation where this activity aims to be able to add insight and can be a provision in the future for students who want to work directly in restaurants. The implementation is carried out online through the Google Meet platform as a support for activities that everyone can easily access. There is a preparation stage and an implementation stage (online training). Basic Service Training Activities in Restaurants for Emmanuel Foundation Students: cleanliness and sanitation are running well and systematically according to the schedule of events that have been made. The pre-test and post-test sessions had the same ten questions. The pre-test was used to see the understanding of Emmanuel Foundation students regarding hygiene and sanitation materials. The post-test was used to see whether or not there was an increase in the knowledge of the Emmanuel Foundation students after the material was presented. This proves that comparing these values is invalid because the significance value is more significant than 0.05. Therefore, the training on the basics of service in restaurants for Emmanuel Foundation students has failed. Therefore, evaluate the process of this training activity so that students have a deeper understanding of the material and practice it directly, gaining knowledge to work in this field in the future and in real-time.